E-036 Idiopathic intracranial hypertension evaluation and treatment: patient selection, venous sinus stenting technique, and post-stenting follow-up protocol: university of colorado technique. (23rd July 2017) - Case, D; Seinfeld, J; Roark, C; Kumpe, D
Abstract : Introduction: Idiopathic Intracranial Hypertension (IIH) is associated with dural sinus outflow obstruction in an unknown percentage of patients. It can cured by venous sinus stent placement, and an increasing number of neurointerventionalists are interested in or beginning to perform the procedure. We describe selection criteria, stenting technique, and post-stenting follow-up for IIH patients at our institution. Methods: Patient charts, selection criteria, operative/procedure notes, and post-stenting follow-up records from January 1999 to March 2017 were reviewed, during which time we deployed 53 stents in 40 patients. Eight patients underwent one to three restenting procedures. Results: Pre-procedure selection criteria: Patients have an established diagnosis of IIH, preferably made by a neuro-optholmolagist, with clearly documented papilledema and lumbar puncture opening pressure >25 cm H20. Usually diagnostic workup and stent placement are not technically difficult. However, we have modified our techniques over time to increase diagnostic accuracy and to simplify the procedure. In the presentation we will expand on some of the points below. Diagnostic procedure: Full strength contrast, higher injection volumes, at least four biplane orthogonal and oblique projections with steep Towne and angled lateral projections are performed in both ICAs. Minimal sedation during the diagnostic evaluation (avoids alterations in dural venous sinus pressures). The type of transverse - sigmoid sinus narrowing (intraluminal filling defect or extrinsic compression) is best seen on the anterior oblique projection ipsilateral to the sinus to be stented. Pressure measurements: 5F Envoy positioned in upper internal jugular vein on the side chosen for stent (dominant sinus). Pressure measurements performed through 027 microcatheter. Pressure in upper IJ measured, then microcatheter is advanced into anterior SSS. Pullback pressure measurements at ≥7 points in the dural sinuses. Dural sinus venography (microcatheter) in the posterior SSS and TS above the stenosis. Continue pullback pressure measurements. Pressure gradient ≥10 mmHg across the narrowing will be stented. Stenting technique: 7F Shuttle sheath positioned in upper internal jugular vein on the appropriate side (dominant sinus). 027 microcatheter fitted coaxially inside a conduit catheter, typically a Navien 072(Medtronic) advanced through the TS-SS stenosis into the TS. An 018 Zilver stent (typically 6–9 mm diameter, 8 cm length) advanced through conduit catheter. Stent deployed from medial TS through upper SS across the stenosis. Repeat pressure measurements. Successful result is pressure gradient <10 mmHg from the anterior SSS to the IJ. Technique for restenting varies slightly and will be discussed. Post-op followup: : Clinical followup in 1–2 months to assess decrease in papilledema. If papilledema has regressed, angiographic follow-up performed at 6 months, then at two years. If papilledema is unchanged or increased, early angiographic/hemodynamic evaluation performed for restenting evaluation. Hemodynamic success is a pressure gradient <10 mmHg between the anterior SSS and the ipsilateral IJ. Papilledema has been eliminated in all patients except two late failures who did not undergo restenting. Conclusion: Appropriate patient selection criteria are required for IIH venous sinus stenting. Our endovascular technique and followup protocols have been refined over time, and have led to successful management of our patients. Disclosures: D. Case: None. J. Seinfeld: None. C. Roark: None. D. Kumpe: None.